MOBILE APPLICATION FOR FARMER’s VEGETABLES AND FRUITS FREIGHT TRANSPORTATION SYSTEM (International Journal of Food and Nutritional Sciences, 2022)
There has been tremendous growth in the use of mobile phones over the last few years. There exist several possible approaches to the development of mobile applications. Farmers have a long-standing interest in the efficiency of the transportation system and also cost of shipping farm products to market. In this paper, a novel android based application has been proposed for farmer’s freight transportation system. Growing traffic congestion and the associated externalities require the study of alternative measures to reduce the number of automobiles travelling every day to the city centers, specifically single-occupant vehicles. Decades ago during oil crises in Europe, people were encouraged to share their vehicles. In this paper, a new application has been developed that describes the transportation of goods for farmers like carpooling. Carpooling is a system by which a person shares his or her private vehicle with one or more people that have similar destinations. This social networking application is also called fare-sharing.